Exploiting protein modification systems to boost crop productivity: SUMO proteases in focus. (12th June 2018) - Garrido, Emma; Srivastava, Anjil Kumar; Sadanandom, Ari
Abstract : Genes encoding deSUMOylating proteases in crop plants are more elaborate than in their non-cultivated relatives, pointing towards a role for deSUMOylation in crop productivity. Abstract: In recent years, post-translational modification (PTM) of proteins has emerged as a key process that integrates plant growth and response to a changing environment. During the processes of domestication and breeding, plants were selected for various yield and adaptational characteristics. The post-translational modifier small ubiquitin-like modifier (SUMO) protein is known to have a role in the regulation of a number of these characteristics. Using bioinformatics, we mined the genomes of cereal and Brassica crops and their non-crop relatives Arabidopsis thaliana and Brachypodium distachyon for ubiquitin-like protease (ULP) SUMO protease sequences. We discovered that the SUMO system in cereal crops is disproportionately elaborate in comparison with that in B. distachyon. We use these data to propose deSUMOylation as a mechanism for specificity in the SUMO system.